2022
DOI: 10.1111/dom.14908
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of liraglutide on reducing visceral and ectopic fat in adults with or without type 2 diabetes mellitus: A systematic review and meta‐analysis

Abstract: Aim: To assess the efficacy and safety of liraglutide to reduce visceral and ectopic fat in adults with or without type 2 diabetes mellitus (T2DM).Methods: Four databases were searched up to 6 May 2022 for randomized clinical trials assessing the effect of liraglutide on visceral and ectopic fat. The mean and standard deviation of the values of visceral fat, ectopic fat and body mass index were calculated. Subgroup analyses were performed based on the type of disease (T2DM or non-T2DM), duration of interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…MEDLINE was systematically searched using the keywords ‘epicardial fat’, ‘EAT’ and ‘diabetes’. Recent systematic reviews 56 60 (covering the period of the last 5 years, between 2018 and 2023) were screened for relevant studies. The following inclusion criteria were used:…”
Section: Methodsmentioning
confidence: 99%
“…MEDLINE was systematically searched using the keywords ‘epicardial fat’, ‘EAT’ and ‘diabetes’. Recent systematic reviews 56 60 (covering the period of the last 5 years, between 2018 and 2023) were screened for relevant studies. The following inclusion criteria were used:…”
Section: Methodsmentioning
confidence: 99%
“…A recent systematic review with meta-analysis of 16 RCTs with 845 patients showed that liraglutide leads to a significant and safe reduction of visceral and ectopic liver fat 273 .…”
Section: Long-acting Glp-1 Rasmentioning
confidence: 99%
“…In the past decade, four types of interventions have been proposed to reduce EAT volume, including exercise interventions, dietary interventions, bariatric surgery, and pharmaceutical interventions 129–134 (Figure 3). There have been a number of well‐designed tables summarizing related clinical studies in recent systematic reviews 134–142 …”
Section: Exploration Of Targeting Eat As a Therapeutic Strategymentioning
confidence: 99%
“…There have been a number of well‐designed tables summarizing related clinical studies in recent systematic reviews. 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 …”
Section: Exploration Of Targeting Eat As a Therapeutic Strategymentioning
confidence: 99%